PERLINDUNGAN HUKUM BAGI ANAK KORBAN KEKERASAN SEKSUAL - Pruntus Sudarmaji; Muhamad Hasan Sebyar (INTELIGENSIA MEDIA, 2023)
This research aims to examine legal protection for children who are victims of sexual violence. The research method in this research uses a literature study approach, focusing on theoretical studies, references, scientific literature, as well as reference books and similar research results. Qualitative analysis will be carried out to understand the relationship between theory and practice of the role of law in investigating revealed cases of children as accident victims. The results of this research show that legal protection for children who are victims of sexual crimes involves various forms of assistance such as legal aid, rehabilitation, health services and social security according to their needs. However, there are obstacles, both in terms of legal substance, legal structure, legal culture, as well as the lack of facilities and infrastructure that function optimally. Protection of child victims of sexual crimes requires updating and strengthening the substantive aspects of the law, increasing public awareness, as well as easy access for children to competent legal assistance. Rehabilitation services and psychological support also need to be a priority in their recovery process. Collaboration between the government, private institutions, civil society organizations and other related parties is considered key to providing effective protection for child victims of sexual crimes